Associations between morphokinetic parameters of temporary-arrest embryos and the clinical prognosis in FET cycles - Li Hong-Xing; Pang Yan; Ma Xiao-Ling; Zhang Xue-Hong; Li Wen-qiang; Xi Ya-Ming (Open Medicine, 2022)
Infertility is a major health concern worldwide. This retrospective study aimed to assess the predictive value of the morphokinetic parameters of temporary-arrest embryos for the pregnancy outcomes of women undergoing frozen embryo transfer (FET) cycles. In this study, we evaluated 244 FET cycles with 431 day-4 temporary-arrest embryos. They were categorized into two groups (pregnancy and non-pregnancy) according to the pregnancy outcomes of the women after embryo transfer on day 5, and their fundamental characteristics were compared. The morphokinetic parameters from the time-lapse monitoring system were assessed according to different pregnancy outcomes. The mean number of embryo blastomeres thawed on day 3 in the pregnancy group was 7.47, which was significantly higher than the number in the non-pregnancy group (p < 0.01). Besides, embryos in the non-pregnancy group contained more embryo fragments and lower grades than those in the pregnancy group (p < 0.001). Furthermore, morphokinetic parameters: tPNa, t2, t5, and t5_tPNf showed a statistical difference between the pregnancy and non-pregnancy groups (p < 0.05). Receiver-operating characteristic analysis revealed that the time from pronuclear fading to the 5-cell stage (t5_PNF) predicted the clinical prognosis outcomes (area under the curve = 0.64; 95% confidence interval [CI], 0.58–0.70; p < 0.001). The morphokinetic parameter t5_PNF could be regarded as a potential implantation predictor in our study.